The challenges faced by kindergarten teachers with distance education under the Corona pandemic - Al-Harbi, Fatimah Ali (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the challenges faced by kindergarten teachers with distance education in light of the Corona pandemic, and to achieve the goal of this study, the study followed the analytical descriptive approach, and the study tool was the questionnaire (40) paragraphs, and the researcher verified the validity and reliability of the questionnaire, and the study sample consisted of (161) female teacher, and the results of the study concluded that the challenges faced by kindergarten teachers with distance education in light of the Corona pandemic were high. Speaking and listening during distance education may cause female teachers to be distracted, and one of the most important psychological and social challenges is the lack of training for children before directing distance education to the use of computers for education, the lack of appropriate training on distance education strategies for female teachers during the service, and the researcher recommended a number of recommendations The most important of which was the necessity of informing officials in the Ministry of Education of the results of this study in order to lead kindergarten teachers, and to develop training programs and workshops in order to develop The students are taught technology and develop their knowledge about what is distance education and the mechanism of applying distance education and overcoming challenges in the educational and technological educational process to meet the psychological and social challenges of teachers.
Keywords: challenges; distance education; Corona pandemic; kindergarten; kindergarten teachers